ON MODELLING DISCRETE GEOLOGICAL STRUCTURES AS MARKOV RANDOM FIELDS - Norberg T.; Rosen L.; Baran A.; Baran S. (My University, 2002)
The purpose of this paper is to extend the locally based prediction methodology of BayMar to a global one by modelling discrete spatial structures as Markov random fields. BayMar uses one-dimensional Markov-properties for estimating spatial correlation and Bayesian updating for locally integrating prior and additional information. The methodology of this paper introduces a new estimator of the field parameters based on the maximum likelihood technique for one-dimensional Markov chains. This makes the estimator straightforward to calculate also when there is a large amount of missing observations, which often is the case in geological applications. We make simulations (both unconditional and conditional on the observed data) and maximum a posteriori predictions (restorations) of the non-observed data using Markov chain Monte Carlo methods, in the restoration case by employing simulated annealing. The described method gives satisfactory predictions, while more work is needed in order to simulate, since it appears to have a tendency to overestimate strong spatial dependence. It provides an important development compared to the BayMar-methodology by facilitating global predictions and improved use of sparse data.
Keywords: SIMULATIONS; PREDICTIONS; MARKOV CHAIN MONTE CARLO; SIMULATED ANNEALING; INCOMPLETE OBSERVATIONS